Sero-prevalence of rubella among pregnant women in Sub-Saharan Africa: a meta-analysis. Issue 10 (2nd October 2020) - Kassa, Zemenu Yohannes; Hussen, Siraj; Asnake, Solomon
ABSTRACT: Background : Rubella continues to be a leading cause of vaccine-preventable congenital birth defects and permanent organ damage, especially in developing countries. For women who are infected with the rubella virus (RV) before conception or during the first trimester of pregnancy, the unborn child has up to a 90% probability of developing congenital rubella syndrome. There are limited data on the seroprevalence of the rubella virus among pregnant women in Sub-Saharan Africa. Therefore, the aim of this study was done to determine the pooled seroprevalence of rubella among pregnant women in Sub-Saharan Africa. Methods : The PRISMA guidelines protocol was followed to write the systematic review and meta-analysis. Published studies were searched in Medline, PubMed, Google scholar, advance google and Cochrane Library. The search terms on the databases are: "rubella"OR "rubeo*", "rubella"AND"seroepidemiology", "seroprevalen *" OR "prevalen*", "seroprevalen *" OR "seroimmun*", "rubella antibod*"AND "pregnan*", "seroprevalen *" AND "sub-Saharan Africa".The heterogeneity of studies was weighed using Cochran's Q test and I 2 test statistics. Publication bias was assessed by using Egger's and Begg's test. Results : Twenty-eight studies were included in this meta-analysis. The pooled seroprevalence of anti-RV IgG among pregnant women in Sub-Saharan African was 89.0% (95%CI: 84.6–92.3), and the pooled prevalence of anti-RV IgM among pregnant women in Sub-Saharan Africa was 5.1% (95%CI: 2.6–9.9). Conclusion : This meta-analysis showed that seronegativity and acute infection with RV among pregnant women in sub-Saharan Africa is high compared to other studies and the WHO threshold among women of child-bearing age. This finding calls for primary health care providers to make the community aware of this rubella-susceptible group and its healthcare burden, with the desired outcome that sub-Saharan Africa countries would introduce an implementation strategy for rubella vaccination of pregnant women and women of child-bearing age.